Effect of folic acid supplementation on genomic DNA methylation in patients with colorectal adenoma. Issue 5 (14th April 2005) - Pufulete, M; Al-Ghnaniem, R; Khushal, A; Appleby, P; Harris, N; Gout, S; Emery, P W; Sanders, T A B
Abstract : Background and aims: A low dietary folate intake can cause genomic DNA hypomethylation and may increase the risk of colorectal neoplasia. The hypothesis that folic acid supplementation increases DNA methylation in leucocytes and colorectal mucosa was tested in 31 patients with histologically confirmed colorectal adenoma using a randomised, double blind, placebo controlled, parallel design. Methods: Subjects were randomised to receive either 400 μg/day folic acid supplement (n = 15) or placebo (n = 16) for 10 weeks. Genomic DNA methylation, serum and erythrocyte folate, and plasma homocysteine concentrations were measured at baseline and post intervention. Results: Folic acid supplementation increased serum and erythrocyte folate concentrations by 81% (95% confidence interval (CI) 57–104%; p<0.001 v placebo) and 57% (95% CI 40–74%; p<0.001 v placebo), respectively, and decreased plasma homocysteine concentration by 12% (95% CI 4–20%; p = 0.01 v placebo). Folic acid supplementation resulted in increases in DNA methylation of 31% (95% CI 16–47%; p = 0.05 v placebo) in leucocytes and 25% (95% CI 11–39%; p = 0.09 v placebo) in colonic mucosa. Conclusions: These results suggest that DNA hypomethylation can be reversed by physiological intakes of folic acid.